VERSLAG OOR DIE AARD EN KWALITEIT VAN GODSDIENSONDERRIG OP SKOOL - Plessis, P. J. du (Scriptura, 1982)
Report on the nature and quality of religious education in schools A survey conducted amongst 2120 first year students drawn from two Afrikaans universities (RAU and PUCHO) and one Teachers’ College (GOK), reveals a disturbing picture. The time allocated for this subject is seldom used constructively and teaching methods and presentation leave much to the desired. It is recommended that education authorities give serious attention to this problem, that a higher qualification in Biblical Studies be required for teachers and that Biblical Studies is actively promoted as an examination subject for matric.